Yellow crystal bead embryo, preparation method and application

By using low -cost components such as selenium powder, woodcar powder, and sulfur in yellow crystal, and using high temperature melting and mold pressure molding process, it solves the problems of uneven color and low production efficiency in the preparation of existing yellow crystal preparation. It has achieved efficient and environmentally friendly yellow crystal bead embryo.

CN119371109APending Publication Date: 2025-01-28HUBEI YUXING CRYSTAL JEWELRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411506548.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing yellow crystal preparation process has problems such as color difference, uneven color, pattern, unstable quality and low production efficiency. Due to the rising prices of rare earth cerium oxide and titanium dioxide, production costs remain high.

Method used

Use cheap selenium powder, wood carbon powder, sulfur, and other components to replace traditional manganese powder, oxidation and titanium pink powder, and introduce new preparation processes, including high temperature melting and molding molding. Essence

Benefits of technology

The color uniformity and transparency of the yellow crystal bead embryo are realized, reducing production costs, improving production efficiency, and reducing environmental pollution, which has environmental protection significance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a yellow crystal bead embryo, a preparation method and application. The yellow crystal bead blank is prepared from the following components in parts by mass: 80 to 90 parts of quartz sand, 30 to 40 parts of sodium carbonate, 3 to 8 parts of potassium carbonate, 1 to 4 parts of borax, 0.5 to 1 part of aluminum hydroxide, 1 to 2 parts of sodium fluosilicate, 0.1 to 0.3 part of barium sulfate, 0.15 to 0.3 part of selenium powder, 0.25 to 0.4 part of charcoal powder and 0.1 to 0.2 part of sulfur. Compared with a traditional formula, cheap selenium powder, charcoal powder and sulfur are used as coloring agents in the formula, and the preparation cost of the yellow crystal bead blank is saved. The invention further provides a brand-new preparation method of the yellow crystal bead blank, and the yellow crystal bead blank produced by combining a new formula and a new process is high in transparency, uniform in color, free of color difference and patterns and high in quality stability; the preparation method adopts tank furnace melting and compression molding processes, is suitable for continuous large-scale production, and improves the production efficiency; in the whole preparation process, lead-containing raw materials and harmful chemical substances are avoided, and environmental pollution in the preparation process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of artificial crystal preparation, and in particular to a yellow crystal bead embryo, a preparation method and an application thereof. Background Art

[0002] Citrine is a very popular gemstone, known for its bright yellow color and various symbolic meanings. It is a variant of quartz, the main chemical component of which is silicon dioxide, and it presents a variety of colors due to the different mixed substances it contains. The color of citrine usually ranges from golden yellow to light brown, and its yellow color is due to the presence of water-oxidized iron in it.

[0003] Traditional yellow crystals achieve the purpose of yellowing by introducing manganese powder, cerium oxide and titanium platinum powder into the formula. However, in recent years, the prices of rare earth cerium oxide and titanium dioxide have continued to rise, resulting in high production costs for yellow crystals. In addition, in the existing yellow crystal preparation process, such as the crucible manufacturing process, the yellow crystals produced often have problems such as poor coloring, uneven color, patterns, unstable quality, and low production efficiency.

[0004] Therefore, it is necessary to develop a new formula and preparation process of yellow crystal pearl embryos. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a yellow crystal bead embryo, a preparation method and an application thereof. The yellow crystal bead embryo, based on the traditional formula, adopts cheap selenium powder, charcoal powder and sulfur and other components to replace manganese powder, cerium oxide and titanium dioxide, and introduces a new preparation process for yellow crystal bead embryos. The use of the new formula and the new process can produce yellow crystal bead embryos with uniform color and high transparency, and reduce production costs and improve production efficiency.

[0006] In order to achieve or at least partially achieve the above objectives, the present application provides the following technical solutions:

[0007] In a first aspect, the present application provides a yellow crystal bead embryo, which comprises the following components, calculated by weight:

[0008] 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 parts of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of charcoal powder, and 0.1-0.2 parts of sulfur.

[0009] Preferably, the yellow crystal bead embryo, calculated by mass, includes 85 parts of quartz sand, 35 parts of soda ash, 5 parts of potassium carbonate, 3 parts of borax, 0.8 parts of aluminum hydroxide, 1.5 parts of sodium fluorosilicate, 0.2 parts of barium sulfate, 0.25 parts of selenium powder, 0.33 parts of charcoal powder, and 0.165 parts of sulfur.

[0010] In a second aspect, the present application provides a method for preparing the aforementioned yellow crystal bead embryo, comprising the following steps:

[0011] S1. Prepare the raw materials of crystal bead embryos according to the mass ratio, including 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 parts of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of wood charcoal powder, and 0.1-0.2 parts of sulfur;

[0012] S2. Mixing raw materials such as quartz sand, soda ash, potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, charcoal powder and sulfur in a dry environment to obtain a mixed material;

[0013] S3. The mixed material is heated to 1350-1450°C in a high temperature furnace to completely melt the mixed material to form a uniform yellow color;

[0014] S4. The melted mixture in S3 is poured into a prefabricated bead embryo mold and cooled to room temperature to obtain a rough bead embryo;

[0015] S5. Anneal and polish the rough pearl embryo obtained in S4 to obtain the final yellow crystal pearl embryo.

[0016] In a third aspect, the present application also provides the use of the aforementioned citrine bead embryo in the preparation of artificial crystal.

[0017] The yellow crystal bead embryo, preparation method and application provided in the present application have at least the following beneficial effects compared with the prior art:

[0018] 1. The present application provides yellow crystal bead embryos. During the preparation process, a mixture of selenium powder, charcoal powder and sulfur is gradually added during a high-temperature melting process, so that a uniform distribution of yellow can be achieved, so that the final crystal bead embryo has a consistent color without color difference.

[0019] 2. The preparation method of the yellow crystal bead embryo provided in the present application adopts a pool furnace melting and compression molding process, which is suitable for continuous large-scale production and improves production efficiency; in addition, lead-containing raw materials and harmful chemicals are avoided in the entire preparation process, reducing environmental pollution in the preparation process, which is of environmental significance. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0021] Those skilled in the art will appreciate that, unless otherwise stated, the "said", "the", and "the aforementioned" used in the text of the present application may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application means the presence of the features, steps, and operations, but does not exclude the presence or addition of one or more other features, integers, and steps.

[0022] In the text of this application, the terms "first", "second" and the like are used to distinguish between identical or similar items with substantially the same functions and effects. This is only for the purpose of clearly describing the technical solutions of the embodiments of this application, and shall not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0023] In the present application, the term "room temperature" refers to normal temperature or general temperature, for example, the temperature range may be 15 to 25°C.

[0024] Those skilled in the art will appreciate that, in the examples of the present application, if no specific conditions are specified, the experiments are carried out under conventional conditions or conditions recommended by the manufacturer, and the reagents or instruments used, if no manufacturer is specified, are conventional products that can be purchased commercially.

[0025] The embodiment of the present application uses selenium powder, charcoal powder and sulfur as colorants for yellow crystal bead embryos based on the traditional formula, instead of manganese powder, cerium oxide and titanium dioxide, which greatly reduces the cost of raw materials while ensuring the uniform coloring effect of the crystal bead embryos. At the same time, by optimizing the preparation process of yellow crystal bead embryos, the production efficiency is further improved, which is suitable for large-scale production. Selenium powder, charcoal powder and sulfur adjust the reducing atmosphere during the preparation process, making the preparation process more stable. Lead-free raw materials are used, which will not cause environmental pollution and has environmental protection significance.

[0026] Based on this, the embodiment of the present application provides a yellow crystal bead embryo, which includes the following components, calculated by mass: 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 part of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of charcoal powder, and 0.1-0.2 parts of sulfur.

[0027] In certain preferred embodiments, the yellow crystal bead embryo, calculated by mass, includes 85 parts of quartz sand, 35 parts of soda ash, 5 parts of potassium carbonate, 3 parts of borax, 0.8 parts of aluminum hydroxide, 1.5 parts of sodium fluorosilicate, 0.2 parts of barium sulfate, 0.25 parts of selenium powder, 0.33 parts of charcoal powder, and 0.165 parts of sulfur.

[0028] Based on this, the present application embodiment provides a method for preparing the aforementioned yellow crystal bead embryo, comprising the following steps: S1. preparing crystal bead embryo raw materials according to mass ratio, including 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 part of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of wood charcoal powder, and 0.1-0.2 parts of sulfur; S2. mixing quartz sand, soda ash, , potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, charcoal powder and sulfur and other raw materials are mixed evenly in a dry environment to obtain a mixture; S3. The mixture is heated to 1350-1450°C in a high-temperature furnace to completely melt it to form a uniform yellow color; S4. The melted material in S3 is poured into a prefabricated bead embryo mold, cooled to room temperature, and a rough bead embryo is obtained; S5. The rough bead embryo obtained in S4 is annealed and polished to obtain the final yellow crystal bead embryo.

[0029] In certain embodiments, in S3, the melting time is 4 to 8 hours.

[0030] In some embodiments, in S5, the annealing and polishing treatment time is 3 to 5 minutes.

[0031] Based on this, the embodiments of the present application also provide the use of the aforementioned citrine bead embryo in the preparation of artificial crystal.

[0032] The technical solution of the present application and the technical effects achieved are described in detail below through more specific embodiments.

[0033] Example 1

[0034] This embodiment provides a method for preparing yellow crystal bead embryos, and the specific steps are as follows:

[0035] (1) Prepare the crystal bead embryo raw materials according to the following mass ratio: 85 parts of quartz sand, 35 parts of soda ash, 5 parts of potassium carbonate, 3 parts of borax, 0.8 parts of aluminum hydroxide, 1.5 parts of sodium fluorosilicate, 0.2 parts of barium sulfate, 0.25 parts of selenium powder, 0.33 parts of wood charcoal powder, and 0.165 parts of sulfur;

[0036] (2) mixing quartz sand, soda ash, potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, wood charcoal powder and sulfur in a dry environment to obtain a first mixed material;

[0037] (3) heating the first mixed material to 1400° C. in a high temperature furnace and keeping the temperature for 4 hours to completely melt the first mixed material to form a uniform yellow color;

[0038] (4) pouring the melted first mixed material into a prefabricated bead embryo mold and cooling it to room temperature to obtain a rough bead embryo;

[0039] (5) The rough pearl embryo obtained in the previous step is annealed and polished for 4 minutes each to obtain the final yellow crystal pearl embryo C1.

[0040] Example 2

[0041] This embodiment provides a method for preparing yellow crystal bead embryos, and the specific steps are as follows:

[0042] (1) Prepare the crystal bead embryo raw materials according to the following mass ratio: 80 parts of quartz sand, 32 parts of soda ash, 3 parts of potassium carbonate, 1 part of borax, 1 part of aluminum hydroxide, 2 parts of sodium fluorosilicate, 0.1 part of barium sulfate, 0.15 parts of selenium powder, 0.25 parts of wood charcoal powder, and 0.1 part of sulfur;

[0043] (2) mixing quartz sand, soda ash, potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, wood charcoal powder and sulfur in a dry environment to obtain a second mixed material;

[0044] (3) heating the second mixed material to 1380° C. in a high temperature furnace and keeping the temperature for 3 hours to completely melt the second mixed material to form a uniform yellow color;

[0045] (4) pouring the melted second mixed material into a prefabricated bead embryo mold and cooling it to room temperature to obtain a rough bead embryo;

[0046] (5) The rough pearl embryo obtained in the previous step is annealed and polished for 4 minutes each to obtain the final yellow crystal pearl embryo C2.

[0047] Example 3

[0048] This embodiment provides a method for preparing yellow crystal bead embryos, and the specific steps are as follows:

[0049] (1) Prepare the raw materials of crystal bead embryos according to the following mass ratio: 90 parts of quartz sand, 38 parts of soda ash, 8 parts of potassium carbonate, 2 parts of borax, 0.8 parts of aluminum hydroxide, 2 parts of sodium fluorosilicate, 0.3 parts of barium sulfate, 0.3 parts of selenium powder, 0.4 parts of wood charcoal powder, and 0.2 parts of sulfur;

[0050] (2) mixing quartz sand, soda ash, potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, wood charcoal powder and sulfur in a dry environment to obtain a third mixed material;

[0051] (3) heating the third mixed material to 1450° C. in a high temperature furnace and keeping the temperature for 3 hours to completely melt the third mixed material to form a uniform yellow color;

[0052] (4) pouring the melted third mixed material into a prefabricated bead embryo mold and cooling it to room temperature to obtain a rough bead embryo;

[0053] (5) The rough pearl embryo obtained in the previous step is annealed and polished for 4 minutes to obtain the final yellow crystal pearl embryo C3.

[0054] Example 4

[0055] This embodiment provides a method for preparing yellow crystal bead embryos, and the specific steps are as follows:

[0056] (1) Prepare the crystal bead embryo raw materials according to the following mass ratio: 85 parts of quartz sand, 30 parts of soda ash, 5 parts of potassium carbonate, 3 parts of borax, 0.8 parts of aluminum hydroxide, 1 part of sodium fluorosilicate, 0.1 parts of barium sulfate, 0.15 parts of selenium powder, 0.33 parts of wood charcoal powder, and 0.165 parts of sulfur;

[0057] (2) mixing quartz sand, soda ash, potassium carbonate, borax, aluminum hydroxide, sodium fluorosilicate, barium sulfate, selenium powder, wood charcoal powder and sulfur in a dry environment to obtain a third mixed material;

[0058] (3) heating the fourth mixed material to 1380° C. in a high temperature furnace and keeping the temperature for 3 hours to completely melt the fourth mixed material to form a uniform yellow color;

[0059] (4) pouring the melted fourth mixed material into a prefabricated bead embryo mold and cooling it to room temperature to obtain a rough bead embryo;

[0060] (5) The rough pearl embryo obtained in the previous step is annealed and polished for 4 minutes each to obtain the final yellow crystal pearl embryo C4.

[0061] The yellow crystal pearl embryos C1 to C4 prepared in Examples 1 to 4 were subjected to performance tests, including transparency and color uniformity, refractive index, and Mohs hardness, and the tests were performed according to the following methods:

[0062] (1) Transparency test: First, observe the crystal bead embryo with the naked eye under strong light to see if there are faint, uniform, tiny horizontal stripes or willow-like substances; secondly, use a magnifying glass or microscope to check whether there are defects inside the crystal bead embryo, such as bubbles, cracks or inclusions;

[0063] (2) Color uniformity test: Observe the crystal bead embryo with the naked eye to see if there is color difference or pattern;

[0064] (3) Refractive index test: refer to the method in GB / T 16553 "Identification of Jewelry and Jade", and use a refractometer to measure the refractive index of the crystal bead embryo;

[0065] (4) Mohs hardness test: Refer to the method in standard GB / T 16553 "Identification of Jewelry and Gemstones" and use a Mohs hardness tester to measure the crystal bead embryo.

[0066] (5) The specific performance test results are shown in Table 1 below:

[0067] Table 1

[0068] Example Crystal bead embryo number transparency Color uniformity Refractive Index Mohs hardness Example 1 C1 No bubbles, cracks or debris No color difference or pattern 1.548 5.8 Example 2 C2 No bubbles, cracks or debris No color difference or pattern 1.543 5.7 Example 3 C3 No bubbles, cracks or debris No color difference or pattern 1.550 5.7 Example 4 C4 No bubbles, cracks or debris No color difference or pattern 1.545 5.6

[0069] From the performance test results in Table 1 above, it can be seen that the yellow crystal bead embryos C1 to C4 prepared in the embodiment have high transparency, without bubbles, cracks or other inclusions; the yellow crystal bead embryos are uniformly yellow, without pigments or patterns; the refractive index and hardness of the yellow crystal bead embryos meet the requirements of artificial crystals, and the performance is stable, and can be used as an intermediate material for preparing artificial crystals.

[0070] In summary, the yellow crystal bead embryo product prepared in the embodiment of the present application has uniform color, no patterns, and stable quality; the preparation method of the yellow crystal bead embryo provided in the embodiment of the present application reduces production costs, improves production efficiency, and is suitable for large-scale production.

[0071] The present application is described in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the present application and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. A yellow crystal bead embryo, characterized in that: Calculated by mass, it includes the following components: 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 parts of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of charcoal powder, and 0.1-0.2 parts of sulfur.

2. The yellow crystal bead embryo according to claim 1, characterized in that: The yellow crystal bead embryo, calculated by mass, includes 85 parts of quartz sand, 35 parts of soda ash, 5 parts of potassium carbonate, 3 parts of borax, 0.8 parts of aluminum hydroxide, 1.5 parts of sodium fluorosilicate, 0.2 parts of barium sulfate, 0.25 parts of selenium powder, 0.33 parts of charcoal powder, and 0.165 parts of sulfur.

3. The method for preparing the yellow crystal pearl embryo according to claim 1, characterized in that: The following steps are involved: S1. Prepare the raw materials of crystal bead embryos according to the mass ratio, including 80-90 parts of quartz sand, 30-40 parts of soda ash, 3-8 parts of potassium carbonate, 1-4 parts of borax, 0.5-1 parts of aluminum hydroxide, 1-2 parts of sodium fluorosilicate, 0.1-0.3 parts of barium sulfate, 0.15-0.3 parts of selenium powder, 0.25-0.4 parts of wood charcoal powder, and 0.1-0.2 parts of sulfur; S2. The raw materials in S1 are mixed uniformly in a dry environment to obtain a mixed material; S3. The mixed material is heated to 1350-1450°C in a high temperature furnace to completely melt the mixed material to form a uniform yellow color; S4. The melted mixture in S3 is poured into a prefabricated bead embryo mold and cooled to room temperature to obtain a rough bead embryo; S5. Anneal and polish the rough pearl embryo obtained in S4 to obtain the final yellow crystal pearl embryo.

4. The preparation method according to claim 3, characterized in that: In S3, the melting time is 4 to 8 hours.

5. The preparation method according to claim 3, characterized in that: In S5, the annealing and polishing times are both 3 to 5 minutes.

6. Use of the citrine pearl embryo according to claim 1 or 2 in the preparation of artificial crystal.